Recent progress in cadonilimab research for oncology applications - Dong, Ming-Zhen; Cui, Ming; Zhu, En-Bo; Lin, Ming-Quan; Dong, Guang-Hui; Jin, Guang-Lin; Qu, Lin-Zhuo; Che, Hui-Ying; Guan, Hong-Jian (Frontiers in Immunology, 2026)
Cadonilimab is the first bispecific antibody independently developed in China that simultaneously targets Programmed Cell Death Protein-1 (PD-1) and Cytotoxic T Lymphocyte-Associated Antigen-4 (CTLA-4), marking a significant milestone in both clinical applications and drug development. Through its dual mechanism of action, cadonilimab blocks PD-1 and CTLA-4 signaling pathways concurrently, thereby activating T cells and enhancing antitumor immune responses. Within the tumor microenvironment, cadonilimab promotes effector T-cell infiltration while reducing nonspecific attacks on normal tissues, thus lowering the incidence of immune-related adverse events. In comparison to conventional monospecific antibodies, cadonilimab exhibits superior selectivity and safety. Multiple studies have shown that, either as monotherapy or in combination regimens, cadonilimab exhibits promising antitumor activity and tolerability in refractory solid tumors such as advanced cervical cancer, hepatocellular carcinoma, non-small cell lung cancer, and gastric cancer, with notable efficacy even in patients with low or negative PD-L1 expression. The successful development of cadonilimab not only underscores China’s innovative capabilities in the field of cancer immunotherapy but also provides valuable insights for global drug development and clinical practice. However, most signals derive from phase I/II single-arm or small-sample studies with limited follow-up, and no randomized head-to-head trials have yet confirmed superiority over standard PD-1+CTLA-4 approaches. This review summarizes the mechanism of action, structural characteristics, clinical research progress, and future applications of cadonilimab, with the aim of offering a useful reference for research and clinical treatment while promoting its broader application in oncology.